The individual effects of cetane number, oxygen content or fuel properties on the ignition delay, combustion characteristics, and cyclic variation of a turbocharged CRDI diesel engine – Part 1. (15th September 2017) - Labeckas, Gvidonas; Slavinskas, Stasys; Kanapkienė, Irena
Highlights: Diesel-HRD fuel blends involving ethanol (E) or biodiesel (B) were investigated in a turbocharged CRDI engine. Improved cetane number of fuel blends ambiguously affected the ignition delay and maximum heat release rate. Increased fuel-bound oxygen content enhanced combustion, heat release and in-cylinder pressure at 2500 rpm. Fuel properties almost did not change premixed phase, but affected burn angle MBF 50 and the end of combustion. Burn angles MBF 50 and MBF 90 were 1.0° and 5.7° CADs shorter when using oxygenated blend OE4 (3.6 wt%) at 2000 rpm. Abstract: The study deals with the effects made by individual variation of cetane number, fuel-oxygen content, or widely differing properties of diesel-HRD fuel blends involving ethanol (E) or biodiesel (B) on the ignition delay, combustion phenomenon, maximum heat release rate, and the cyclic variation of a turbocharged CRDI diesel engine. The most important control factors one after another operated separately in this study to make a difference. Load characteristics were taken when running with a straight diesel and various (18) diesel-HRD fuel blends at maximum torque mode of 2000 rpm and speeds of 1500 and 2500 rpm to provide correct interpretation of the test results. Then, load (bmep) characteristics were plotted as a function of the relative air-fuel ratio (λ) and the analysis of combustion parameters was conducted for the 'lambda' values of λ = 1.30, 1.25 and 1.20, at the respective speeds of 1500, 2000 and 2500 rpm. Analysis of changes in the ignition delay, combustion characteristics, and the cyclic variation of parameters when using fuel blends of both origins was performed on comparative bases with the corresponding values measured with 'base-line' blends with CN = 51.2 or zero oxygen content and a straight diesel to reveal the potential developing trends. The enhanced cetane number of oxygenated fuels improved combustion and reduced cyclic variation when running at the high speed of 2500 rpm mainly. Whereas fuel-oxygen content should be neither too high nor too low, but just enough to assure complete combustion and low cyclic variation. The differing properties of the fuel involving ethanol or biodiesel were a separate factor strongly affecting diffusive combustion and the coefficient of cyclic variation (COV). Developing trends in the combustion characteristics were used to interpret the resulting changes in engine performance, emissions, and smoke (Part 2).